Redescription of the type specimens of the Elachista freyerella species-group (Lepidoptera: Elachistidae: Elachistinae) from India and Sri Lanka - Sruoga, Virginijus; Diskus, A. (Zootaxa, 2006)
Five species of the Elachista freyerella species-group from India and Sri Lanka are redescribed based on their types; their genitalia are figured for the first time.